Monitoring of Antimicrobial Resistance to Aminoglycosides and Macrolides in Campylobacter coli and Campylobacter jejuni From Healthy Livestock in Spain (2002–2018) - Lopez-Chavarrias, Vicente; Ugarte-Ruiz, Maria; Barcena, Carmen; Olarra, Adolfo; Garcia, Maria; Saez, Jose Luis; de Frutos, Cristina; Serrano, Tania; Perez, Iratxe; Moreno, Miguel Angel; Dominguez, Lucas; Alvarez, Julio (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) in Campylobacter spp. (Campylobacter coli and C. jejuni) is a concern due to its importance in public health, particularly when it involves aminoglycosides and macrolides, drugs of choice for treatment of human cases. Co-resistance to these two antimicrobial classes involves transfer of genetic elements and/or acquisition of mutations in different genetic loci, which can in turn spread through vertical or horizontal gene transfer phenomena, with each route having different potential implications. This study aimed at evaluating the association between the presence of phenotypic resistance to these two antimicrobial families in C. coli and C.jejuni recovered from livestock at slaughterhouses in Spain (as part of the AMR surveillance program), and at assessing the genetic heterogeneity between resistant and susceptible isolates by analysing the ‘short variable region’ (SVR) of the flaA gene. Over the 2002-2018 period, antimicrobial susceptibility test results from 10,965 Campylobacter isolates retrieved from faecal samples of broilers, turkeys, pigs and cattle were collected to compare the proportion of resistant isolates and the Minimum Inhibitory Concentrations (MICs) against six antimicrobials including gentamicin, streptomycin and erythromycin. The flaA SVR of a subset of 125 isolates from all hosts with different resistotypes was sequenced to build a Neighbor-Joining-based phylogenetic tree and assess the existence of groups by means of ‘relative synonymous codon usage’ (RSCU) analysis. The proportion of antimicrobial resistant isolates to aminoglycosides and macrolides varied widely for C. coli (poultry 7-56%, cattle 12-82% and pigs 22-91%) and less for C. jejuni (all hosts 0-11%). Comparison of the MIC distributions revealed significant host-specific differences only for erythromycin in C. jejuni (p=0.032). A significant association in the simultaneous presentation of AMR to both antimicrobial families was observed across hosts/bacterial species. The flaA gene analysis showed clustering of isolates sharing certain characteristics (mostly resistotype and to a lesser degree bacterial species and host). The consistent association between the simultaneous presentation of AMR to aminoglycosides and macrolides in all hosts and the preliminary genetic assessment suggests the possible persistence of strains/resistance mechanisms in Campylobacter populations in livestock over time. Further studies based on whole genome sequencing are needed to confirm these results.